Student Views of BK Teacher Profiles in Terms of BK Professional Ethics - Salma Nur Maulida; Nandang Budiman; Nadia Aulia Nadhirah (Journal of Education and Counseling (JECO), 2023)
The complexity of problems in everyday life is a challenge for school counselors and counselors in demonstrating their professionalism as a counselor profession in assisting counselee development. For the sake of maintaining honor as profession, so as school counselor must aware that for reach That need competency and obey to code ethics profession. Student as user service counseling in school still looked bad profile from the school counselor. The purpose of this research is to know view from student to counselor profiles and how ethics profession real school counselor. On study in this case, the method used is method SLRs which one _ writer succeed collect 30 articles with 4 articles including the focus on the results for studied related view student to the school counselor. After data and articles were collected next will analyzed in this way this research gets a conclusion. The results obtained in the research of 4 Articles that have been reviewed have positive results and some are negative. This can be taken from the selected literature, one of which is that there are still many students who consider school counselors to be "school police". This shows that less good profile from the school counselor in the view of the student. In fact, it still is often happening error in gift service counseling, which usually done by school counselor in school That Alone. However, from some literature, the school counselor's profile is considered good, close to students and can be trusted to tell personal things. As for study about application ethics or code Guidance Counseling ethics shows the understanding of the school counselor on the guidance and counseling teacher's code of ethics is relatively low.